2009
DOI: 10.1080/10538710902902679
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Childhood Sexual Abuse and Sexual Dysfunction in Jamaican Adults

Abstract: This study examined the associations between early traumatic sexualization and later sexual dysfunction in a sample of 100 Jamaican adults while identifying the linkages between age, frequency of abuse, and gender on sexual functioning. Participants were selected via purposive and convenience sampling and divided equally into comparison and experimental groups based on sociodemographic characteristics. Results indicated that childhood sexual abuse is a likely factor in the development of sexual dysfunction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…To this purpose, sexual dysfunction following trauma exposure has been reported in post-traumatic stress disorders [48] and found associated with disrupted childhood attachment [28] . In line with this previous evidence and our present findings, long-lasting adverse relationship with attachment figures and the perception of neglect have been reported influential to later sexual dysfunction [49,50] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this purpose, sexual dysfunction following trauma exposure has been reported in post-traumatic stress disorders [48] and found associated with disrupted childhood attachment [28] . In line with this previous evidence and our present findings, long-lasting adverse relationship with attachment figures and the perception of neglect have been reported influential to later sexual dysfunction [49,50] .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, adverse childhood experiences and poor parenting have been repeatedly demonstrated to be associated with substance abuse and risky personality traits in the adults [24][25][26][27] and could also negatively influence sexual function. To this purpose, disrupted childhood attachment was commonly found in a sample of men with erectile dysfunction, and this reported association with significant differences in their clinical profile, including an earlier onset, a lower likelihood of being married and higher rates of performance anxiety [28] . Childhood adversities such as sexual abuse were identified as a likely factor in the development of sexual dysfunction in adults [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Is the use of self-administered questionnaires really helpful in the evaluation at pretreatment of neurotic patients with accompanying sexual dysfunction? Other investigators, particularly in Polish studies [40], have reported predominantly on data from questionnaires devoted to certain sexual dysfunctions [20][21] and to specific subpopulations [17][18]36].…”
Section: Discussionmentioning
confidence: 99%
“…They affect orgasm and/or sexual drive, disturb relationships [18], and predict vestibulodynia [19], dyspareunia [20], and vulvodynia [21]. For instance, the latter is estimated 4.4 times more likely to be reported if the perpetrator was a primary family member, and 6.5 times if the abuse was frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of literature on CSA in Jamaica among MSM, the current study sought to add to the literature on the experiences of CSA among MSM survivors (Fields et al, 2008;Swaby & Morgan, 2009). Men in this sample also described how these experiences have led to continued psychosexual trauma which extended into adulthood (Hornor, 2010).…”
mentioning
confidence: 99%